Lepromatous leprosy, melanoma, and basal cell carcinoma: clinical-histopathologic association - Braghiroli, Cintia Santos [UNESP]; Parise-Fortes, Maria Rita [UNESP]; Alencar Marques, Mariangela Esther [UNESP]; Lastoria, Joel Carlos [UNESP] (Soc Brasileira Dermatologia, 2019)
Cutaneous neoplasms frequently occur in leprosy, but there are few reports of the coexistence of leprosy and basal cell carcinoma in the same lesion. This case reports a 49 year-old male with an ulcerated plaque on the right lateral nasal wall, bright papules on the sternal region, and a blackened plaque on the right temporal region. The nasal and temporal lesions were diagnosed by histopathology as basal cell carcinoma and melanoma, respectively. The sternal lesions were excised with the repair of the dog ear which histopathological examination showed macrophages in the dermis parasitized with acid-fast bacilli, confirming the diagnosis of lepromatous leprosy with Fite-Faraco staining. This case report highlights the importance of referring the dog-ear specimen for histopathologic analysis. (C) 2019 Published by Elsevier Espana, S.L.U. on behalf of Sociedade Brasileira de Dermatologia.
Keywords: Carcinoma; basal cell; Leprosy; Melanoma